Predator size interacts with habitat structure to determine the allometric scaling of the functional response. Issue 3 (7th September 2012) - Toscano, Benjamin J.; Griffen, Blaine D.
<x xml:space="preserve">Abstract</x> While both predator body size and prey refuge provided by habitat structure have been established as major factors influencing the functional response (per capita consumption rate as a function of prey density), potential interactions between these factors have rarely been explored. Using a crab predator (Panopeus herbstii) – mussel prey (Brachidontes exustus) system, we examined the allometric scaling of the functional response in oyster (Crassostrea virginica) reef habitat, where crevices within oyster clusters provide mussels refuge from predation. A field survey of mussel distribution showed that mussels attach closer to the cluster periphery at high mussel density, indicating the potential for saturation of the refuge. In functional response experiments, the consumption rate of large crabs was depressed at low prey density relative to small crabs, while at high prey density the reverse was true. Specifically, the attack rate coefficient and handling time both decreased non‐linearly with crab size. An additional manipulation revealed that at low prey densities, the ability of large crabs to maneuver their claws and bodies to extract mussels from crevices was inhibited relative to small crabs by the structured habitat, reducing their attack rate. At high prey densities, crevices were saturated, forcing mussels to the edge of clusters where crabs were only limited by handling time. Our study illuminates a potentially general mechanism where the quality of the prey refuge provided by habitat structure is dependent on the relative size of the predator. Thus anthropogenic influences that alter the natural crab size distribution or degrade reef habitat structure could threaten the long‐term stability of the crab –mussel interaction in reefs.